Risiko Produksi Komoditas Pakcoy di CV Bumi Agro Technology Kebun Baruajak, Kecamatan Lembang - Adriel, Jonathan; Sadeli, Agriani Hermita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Brasiica rapa L. or as known pakcoy is one of vegetable that are many produced in Indonesia. Central Bureau of Statistics shows the production of pakcoy keep increasing especially in West Java Province. West Java specifically in Bandung experienced in increasment of pakcoy production, one of the district that contribute to the increasement is West Bandung district. CV Bumi Agrotechnology is one of company that moves in agriculture which produce vegetables in Lembang District. One of the prominent vegetable commodities is pakcoy, which is ordered by partners. The problem faced by the company is identified which is production risk that interfere with the ongoing pakcoy production activities. The objective of this research is to identified the risk event, risk agent, and what mitigation measures can be taken to deal with pakcoy risk production at CV Bumi Agrotechnology. The design of this research uses qualitative design by using interview method to the person in charge of the company and House of Risk analysis. The results show that there are several risk event and risk agent that must be prioritized because they disrupt the production activities. There are four mitigation action can be taken with the most iimprotant is to improve human resources and farmimng tools quality.